The Big Milly-Molly-Mandy Storybook - Brisley, Joyce Lankester; Illustrated by Vulliamy, Clara (London Kingfisher, 2000)
A special slipcase edition of a much-loved classic character.
Include Color Illustrations
Keywords: Milly-Molly-Mandy (Fictitious character) -- Girls -- Village communities